The Influence Of Information Technology, Tax System Fairness, And The Quality Of Tax Authorities' Services On The Tax Rate Evasion (Case Study at KPP Pratama Kembangan) - Giren Alviansah; Muhyarsyah (Proceeding International Annual Conference Economics, Management, Business, and Accounting, 2023)
This study aims to examine the influence of the information technology, tax system fairness and the quality of fiscus services on tax evasion case studies at KPP Pratama Kembangan. The population in this study are individual taxpayers registered with the KPP Pratama Kembangan in 2022. The sampling technique in this study used accidental sampling. The research data was sourced from questionnaires shared with respondents. The data analysis method used is multiple linear regression analysis, while data processing uses SPSS. The results showed that information technology has a negative effect on tax evasion. The fairness of the tax system affects tax evasion. The quality of fiscus services affects tax evasion.